Structural positions, hierarchies, and perceptions of gender equality - Mihajlović Trbovc, Jovana (Družboslovne razprave, 2022)
Based on a study of gender equality issues in a research organisation in an Eastern European post-socialist country, the paper argues that the increasing precariousness of academic employment and project-based work lead to workplace dynamics that must be considered in a specific setting. The results of a survey of employees at ZRC SAZU show how one‘s position within the academic hierarchy and structure, as well as the nature of the work regime, shape employees‘ opinions. The largest differences in opinion exist between junior female researchers and senior male ones, but there are also relevant differences in the views of women working as research and as administrative staff. The results indicate that an analysis that takes into account the forces of the neoliberal academic market has the potential to illuminate regimes of inequality that are gendered through the relationship between work and social reproduction rather than through identity categories as such.
Keywords: enakost spolov; gender equality; intersectionality; intersekcionalnost; precarious employment; prekarno delo; research centres; Slovenia; Slovenija; znanstvenoraziskovalni centri